Pedagogical Competencies in the Age of Artificial Intelligence: Social, Ethical, and Educational Perspectives - Tartari, Elda; Çerma, Uendi (European Journal of Social Science Education and Research, 2026)
Three dimensions: digital transformation, pedagogical competencies, and ethical governance are used in this study to investigate the integration of artificial intelligence (AI) in teaching and learning. By applying a PRISMA-informed systematic literature review approach, the study synthesises theoretical and empirical research to provide an overview of how AI can change educational practices and teachers’ professional roles. The review highlights how AI-powered technologies, such as machine learning, personalized learning systems, automated assessments, and feedback mechanisms, can positively address the evolving needs of teacher competence. The results show that integrating AI into teaching requires teachers to develop advanced digital and pedagogical competencies, as well as their ability to evaluate AI-generated outcomes responsibly, particularly concerning data privacy, fairness, and accountability. It also emphasizes the role of educational organizations in developing governance structures, professional development processes, and educational policies. By combining various research, this study presents a human-centered approach to AI integration and offers an overview for future research and practical applications in digitally transformed educational settings.